(untitled) (Eureka Journal of Civil, Architecture and Urban Studies, 2026)
This article analyzes the process of transition from “sustainable development” to “regenerative (renewable) design” in modern architecture and urban planning, its theoretical foundations and application possibilities in the conditions of Uzbekistan. The difference of regenerative architecture from traditional green construction, its role in restoring ecosystems, creating carbon-negative buildings and enriching the social environment are revealed. According to the results of the research, it is possible to form climate-resistant, energy-independent and environmentally beneficial spaces by combining national architectural traditions with modern biomimicry and circular economy principles. At the end of the article, practical proposals for the development of the field are presented.